Flood Insurance and Risk Reduction: Market Penetration, Coverage, and Mitigation in Coastal North Carolina. (8th March 2019) - Ahmadiani, Mona; Ferreira, Susana; Landry, Craig E.
Abstract : This article provides an overview of flood risk management in the United States, focusing on the National Flood Insurance Program and the Community Ratings System (CRS), which is designed to promote flood hazard mitigation. We review the empirical literature that examines market penetration and demand for flood insurance, as well as factors that influence community participation in CRS. Combining data from separate (but similar) surveys conducted in Dare County, North Carolina in 1998 and 2008, we examine trends in flood insurance holdings and explore the extensive (binary participation) and intensive (coverage level) margins using regression analysis. We explore trends in CRS mitigation activities in Dare County and discuss potential difficulties in analyzing these data. Finally, we highlight avenues for future research.